The Influence of Coronavirus (Covid-19) Outbreaks on Tourist’s Destination Choice - Barazi, Lamya; Alshareef, Fardaows; Saigh, Mona; Alamri, Raghad Abdulaziz (Journal of Tourism Management Research, 2020)
Little information about the impact of pandemic/epidemic on tourist’s choice of destination. The current study aims to investigate the impact of six factors following the COVID-19 pandemic. Drawing on a sample of 504 Saudis who had a domestic /international travel experience was utilized to collect the data throughout the online survey. While respondents of the research display a high self-efficacy on travel, they demonstrate a moderate perception of tourism services, perception of susceptibility, perception of travel risk, a panic of crisis in destination, and perception of tourism activities in the destination. The finding of the study shows some significant differences between genders on perception of these six dimensions. The results express that even after the ban is lifted, Saudi tourists perceive domestic travel as risky as international travel. Females appear to be more travel avoidance than males because of the outbreak of (COVID-19) pandemic. In addition, females appear to have a higher panic of dying because of having coronavirus disease (COVID-19) during international and domestic travel.